2014
DOI: 10.1049/iet-com.2013.0828
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on power line communication in aircrafts

Abstract: Power line communication is envisaged for the future more electric aircraft and the scenario studied in this work deals with the cabin lighting system, since its tree-shaped architecture is sufficiently complicated to be representative of many other aircraft harness configurations. The statistical characteristics of the propagation channels are deduced from the measurements made on a representative test bench, the experimental values of the insertion gain being also compared with those obtained from a theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…They also estimated the expected throughput of different links [133]. Furthermore, fieldprogrammable gate array-based modems were designed, and the performance of the links was investigated by Degardin et al in [134], who showed that the BER does not exceed 2 × 10 −4 at a bit rate below 91 Mbps. • Optical Wireless Networks: Optical wireless networking offers the potential of exploiting a relatively untapped region of the electromagnetic spectrum for communication, by exploiting Light Emitting Diodes (LEDs) for information transmission [135].…”
Section: In-cabin Communicationsmentioning
confidence: 99%
“…They also estimated the expected throughput of different links [133]. Furthermore, fieldprogrammable gate array-based modems were designed, and the performance of the links was investigated by Degardin et al in [134], who showed that the BER does not exceed 2 × 10 −4 at a bit rate below 91 Mbps. • Optical Wireless Networks: Optical wireless networking offers the potential of exploiting a relatively untapped region of the electromagnetic spectrum for communication, by exploiting Light Emitting Diodes (LEDs) for information transmission [135].…”
Section: In-cabin Communicationsmentioning
confidence: 99%
“…It is worth mentioning that, for the CLS configuration and using the PHY layer described in [31], the predicted throughput for a target BER of 10 -3 reaches, for the worst link, 78 Mbits/s, this value being experimentally confirmed. The next step for assessing PLC in A/C and S/C is to take into account operational/safety aspects and compliance with real time constraints, as latency.…”
Section: Figure 10 Cumulative Distribution Function Of Common Mode Rmentioning
confidence: 56%
“…A representative CLS tree shaped architecture shown in Fig. 8, leads to a network of 38 branches [31], [32].…”
Section: Iii2 Aircraftmentioning
confidence: 99%
See 1 more Smart Citation
“…The reading lamps can be connected to the external communications system by any technology (e.g., power line communication [3] or optical fiber [4]). Each user device logs on to "its own" cell through a proper uplink transmission protocol (typically infrared, IR).…”
Section: Introductionmentioning
confidence: 99%